TOXICOLOGICAL RESPONSE OF THE BLUEGREEN ALGA OSCILLATORIA AGARDHII, TO HEAVY METALS - NAMITA SIKARWAR; G P SINGH (International Journal of Pharma and Bio Sciences, 2012)
Problems statement: The disturbance of aquatic ecosystems provoked by heavy metals pollution from industrial and domestic sources has as consequence the loss of biological diversity, as well as increased bioaccumulation and magnification of toxicants in the food chain. The aim of this study was to evaluate the effect of some heavy metals on some physiological activities of Oscillatoria agardhii with special references to metal bioaccumulation. Approach: Oscillatoria agardhii was isolated from Jalmahal lake,Jaipur. A standard initial inoculum of the isolated algae was inoculated to culture flasks. The culture flasks were supplied with various concentrations of Cobalt and Zinc ranging from 1.5 ppm 2.5 ppm 3.5 ppm & 5 ppm At the end of the incubation period cultures were filtered and washed several times by distilled water for measurements the various experimental parameters. Results: The data show that the lower doses of the tested metals had stimulatory effect in biomass yield of Oscillatoria agardhii, whereas the higher doses were inhibitory depending on the type of the metal. On the other hand, bioaccumulation of cobalt and zinc by Oscillatoria agardhii cells were parallel to increasing the concentrations in the culture medium. Conclusion: The inhibitory and stimulatory effects of either of the used heavy metals depend on concentration. Different organisms, however, have different sensitivities to the same metal and the same organisms may be more or less damaged by different metals. The uptake of an element from the surrounding medium is seldom exactly proportional to the amount present in the water.